1998
DOI: 10.1161/01.atv.18.2.244
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exertion Induces Thrombin Formation and Fibrin Degradation in Patients With Peripheral Atherosclerosis

Abstract: Abstract-Sudden extreme physical stress is associated with an increased risk of myocardial infarction mainly in people with preexisting atherosclerosis. In this study we compared the effect of submaximal exercise on coagulation and fibrinolysis in patients with peripheral arterial occlusive disease (PAOD) with that in healthy control subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 49 publications
3
60
0
1
Order By: Relevance
“…25 However, in a separate study, submaximal exercise in PAD patients with intermittent claudication was associated with an acute increase in thrombin formation. 26 Thus, associations between exercise and pro-thrombotic markers in patients with PAD are unclear.…”
Section: à21mentioning
confidence: 99%
“…25 However, in a separate study, submaximal exercise in PAD patients with intermittent claudication was associated with an acute increase in thrombin formation. 26 Thus, associations between exercise and pro-thrombotic markers in patients with PAD are unclear.…”
Section: à21mentioning
confidence: 99%
“…12 In most studies, baseline D-dimer levels are reported to be higher in claudicants compared to healthy controls. 2,16,19,20 D-dimer levels significantly increase after exercise compared to the respective levels of healthy controls, 2,16,19,20 and it appears to persist up to 1 h postexercise. 2 This increase is not significant when compared to the baseline values.…”
Section: Discussionmentioning
confidence: 86%
“…It is not clear if tPA or PAI-1 activity overwhelms the other, but to a degree a balance between the two antagonizing effects is reached. 16 Ratios between the tPA and PAI-1 activity and antigen levels would be useful to explore the state of balance, but unfortunately these are not used but in one of the already mentioned studies. 16 If we consider the few available data on post-exertion antigen valid, post-exertion tPA Ag concentration appears to decrease and PAI-1 Ag concentration appears to remain stable, 12,15 meaning a degree of clotting degradation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vinogradsky et al (39) found abundant expression of PAT-1 in the atherosclerotic vascular wall. Further, attenuated fibrinolytic activity characterized as elevated circulating levels of PAI-1 has been frequently detected in patients with coronary artery disease (40) and peripheral vascular disease (41). In addition, increased plasma fibrinolytic activity and plasma clotlysis have been demonstrated in homozygous PAI-1-deficient mice (42).…”
Section: Fibrinolysismentioning
confidence: 99%